Angular offset distributions during fixation are, more often than not, multimodal - Lee Friedman; Dillon James Lohr; Oleg V Komogortsev; Timothy Hanson (Bern Open Publishing, 2021)
Typically, the position error of an eye-tracking device is measured as the distance of the eye-position from the target position in two-dimensional space (angular offset).  Accuracy is the mean angular offset.  The mean is a highly interpretable measure of central tendency if the underlying error distribution is unimodal and normal. However, in the context of an underlying multimodal distribution, the mean is less interpretable. We will present evidence that the majority of such distributions are multimodal.  Only 14.7% of fixation angular offset distributions  were  unimodal, and  of  these,  only  11.5%  were normally distributed.  (Of the entire dataset, 1.7% were unimodal and normal.)  This multimodality is true even if there is only a single, continuous tracking fixation segment per trial. We present several approaches to measure accuracy in the face of multimodality. We also address the role of fixation drift in partially explaining multimodality.